The Effect of Compensation on Employee Work Effectiveness at the Bima Regency Tourism Office - Ade Febryanti; Amirulmukminin Amirulmukminin (Universitas Muhammadiyah Makassar, 2023)
This research is associative research. That is looking at the relationship between the effect of compensation on the work effectiveness of employees at the tourism office of Bima Regency. The number of samples in this study were 48 people who are civil servants in the scope of the Tourism Office of Bima Regency with the sampling technique used is purposive sampling. This technique is used with the consideration that only employees with civil servant status receive compensation. From the results of the data analysis on the questionnaire given, all the statements compiled are valid and also reliable. So from the analysis of the data on the respondents, it was obtained that = 3.754 ttable = 1.678 or seen from. p value (sig.) 0.000 = 0.05¸then compensation has a significant effect on work effectiveness (Ha is accepted). In addition, the relationship between the two variables is also in the range or strong category with a value of 0.79, while the flow rate is 50.3%.